EFEKTIVITAS PEMBELAJARAN BERBASIS PROYEK (PROJECT-BASED LEARNING) DALAM MENUMBUHKAN KEMANDIRIAN BELAJAR SISWA MADRASAH IBTIDAIYAH - Fenni Yuniasari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model in fostering learning independence among students of Madrasah Ibtidaiyah (Islamic Elementary School). Learning independence is a crucial indicator in shaping students’ character, enabling them to learn actively, independently, and responsibly. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation at a Madrasah Ibtidaiyah that has implemented PjBL in its instructional activities. The results reveal that the systematic implementation of PjBL through stages including project formulation, planning, execution, evaluation, and reflection enhances students’ active participation in the learning process. Students showed significant improvement in learning initiative, time management, decision-making, and self-reflection. Supporting factors in the successful implementation of PjBL include teacher competence, school management support, and parental involvement. Meanwhile, inhibiting factors consist of limited facilities, varied student abilities, and constrained instructional time. Thus, Project-Based Learning is proven to be effective in cultivating learning independence among elementary-level students, although it requires systemic support from various stakeholders.